Assessment of prenatal depression among U.S. pregnant women without access to paid sick leave and regular place of care: National Health Interview Survey of U.S.-born and non-U.S.-born - Saanie Sulley; David Adzrago; Lohuwa Mamudu; Emmanuel A. Odame; Paul H. Atandoh; Ishmael Tagoe; David Ruggieri; Lisa Kahle; Faustine Williams (Preventive Medicine Reports, 2023)
Prenatal depression is one of the most common risks during pregnancy. This study examined the prevalence and likelihood of prenatal depression association with sociodemographic factors, paid sick leave, and place of care among U.S. pregnant women. We conducted bivariate Chi-square tests to assess the statistical difference and multivariable logistic regression models to assess the association of prenatal depression using the National Health Interview Survey, cross-sectional data from 2010 to 2019 of pregnant women aged 18–44 years (N = 957). The prevalence of prenatal depression was 40.6%, 28.5%, and 27.2% among White, Black, and other racial pregnant women, respectively. Pregnant women with no regular/routine place of care had a prenatal depression prevalence rate of 58.1%, and those without access to paid sick leave had 46.9%. Also, pregnant women without access to paid sick leave were found to have an increased likelihood of reporting prenatal depression ([adjusted odds ratio] AOR = 2.50, 95% CI = 1.72–3.64), as well as those without a regular place of care (AOR = 2.43, 95% CI = 1.32–4.47). The findings identify factors that need to be addressed to minimize depression among U.S. pregnant women and establish the need for tailored interventions to address prenatal depression.